Strengthening Fishermen’s Leadership of Puspita Bahari Community for Supporting Blue Economy in Demak Regency - Putra, Riza Andesca; Dewi, Tevana Sari; Prasaja, Andre Dwi (POLITEA, 2023)
The situation of fishermen in Morodemak Village. Demak Regency is the same as that of fishermen in general. The situation of women can be said to be “powerless” socially, economically, and culturally. The patriarchal system limits women’s rights, resulting in restrictions on women’s rights outside of family affairs. Gender issues are a major issue in the realm of development, especially human resource and economic development. Blue economy is a concept that describes economic activities that not only reduce waste, but also improve the community’s economy. This research uses descriptive qualitative research methods, and purposive sampling technique to determine informants. Data analysis used the three-stage Miles and Huberman model, namely data reduction, data presentation, and conclusion drawing. Coastal communities are part of a pluralistic society, but still have a strong sense of solidarity. Puspita Bahari Communit’s struggle is not only about creating equal conditions, but also about strengthening the role of women in the group, respecting tradisional knowledge and skills, and actively participating in resource management and sustainable development in the region. The future opportunity is that Puspita Bahari Community could become a kind of replication , if it is institutionally good, shows clear outputs, and has a sustainable program. Then the blue economy becomes an alternative solution to strengthen and empower fisherwomen independently.